2008
DOI: 10.1016/j.biopsych.2008.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Corpus Callosum Integrity in Bipolar Disorder: A Diffusion Tensor Imaging Study

Abstract: Objective-Abnormalities in the anterior interhemispheric connections provided by the corpus callosum (CC) have long been implicated in bipolar disorder (BD). In this study, we used complementary diffusion tensor imaging (DTI) methods to study the structural integrity of the CC and localization of potential abnormalities in BD. Methods-Subjects included 33 participants with BD and 40 healthy comparison participants.Fractional anisotropy (FA) measures were compared between groups using region of interest (ROI) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
105
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(121 citation statements)
references
References 18 publications
14
105
0
2
Order By: Relevance
“…However, several neurological diseases often affect the fiber composition and integrity of the corpus callosum, and several studies have reported morphological and microstructural changes of the corpus callosum in patients with neurological diseases, such as autism, 45,46 schizophrenia, 47 and bipolar disorder. 48 In these diseases, abnormal interhemispheric connectivity is suggested, and the noninvasive measurement of axonal properties of the corpus callosum could provide useful information.…”
Section: In Vivo Experiments In Healthy Volunteersmentioning
confidence: 99%
“…However, several neurological diseases often affect the fiber composition and integrity of the corpus callosum, and several studies have reported morphological and microstructural changes of the corpus callosum in patients with neurological diseases, such as autism, 45,46 schizophrenia, 47 and bipolar disorder. 48 In these diseases, abnormal interhemispheric connectivity is suggested, and the noninvasive measurement of axonal properties of the corpus callosum could provide useful information.…”
Section: In Vivo Experiments In Healthy Volunteersmentioning
confidence: 99%
“…56,57 Three recent studies implemented a TBSS analysis in patients with bipolar disorder. This method avoids some limitations of classic ROI analyses, notably the operator dependency, the time-consuming manual ROI selection and the difficulty of delineating the ROI borders unequivocally.…”
Section: White Matter Changes In Patients With Bipolar Disordermentioning
confidence: 99%
“…Our study is the DWI study focusing on patients with Even though recent studies have shown increased (17) or decreased (18,19) corpus callosum fractional anisotrophy (FA) values, these results seems to be contradictory. In our study, an important limitation was the absence of DWI data from other sub-regions of corpus callosum, including anterior body, posterior body, and splenium.…”
Section: Discussion Adc Measurementsmentioning
confidence: 97%